EXPLORING THE PEDAGOGICAL ASPECTS OF MICROLEARNING IN EDUCATIONAL SETTINGS: A SYSTEMATIC LITERATURE REVIEW (Malaysian Journal of Learning and Instruction, 2023)
Purpose - Technology has revolutionized education, leading to innovative learning techniques like microlearning. Microlearningis gaining popularity in higher education and corporate settings for its student-centred approach and well-planned modules. However,its pedagogical design is complex, requiring a systematic review of studies to identify effective practices. The purpose of this study is to conduct a systematic literature review to identify effective practices of microlearning in teaching and learning in higher education between 2014 and 2023. The study aims to analyse the pedagogical design of microlearning in educational settings.Methodology - The study follows the Preferred Reporting Items for Systematic Review and Meta-Analysis (PRISMA) guidelines.A systematic literature review was conducted to identify, evaluate, interpret, and analyse available studies on the practices of microlearning. The analysis focused on the research question and identified themes related to the pedagogical design of microlearning.Findings - The analysis revealed two final themes: the design of microlearning content and instructional flow. The design of microlearning content focused on developing microlearning material, while instructional flow focused on organizing content learning.These findings provide insights into effective practices for curriculum designers and instructors in designing and developing microlearning strategies in teaching and learning.Significance - The findings of this study have significant implications for educators and curriculum designers. The study highlights theimportance of considering both the design of microlearning content and instructional flow in creating engaging and effective microlearning experiences for students in higher education. By incorporating these findings, educators and curriculum designers can enhance the quality of microlearning strategies in teaching and learning.